System for evaporating final discharge wastewater generated in a palm oil mill - Hassan, Mohd Ali; Shirai, Yoshito; Sulaiman, Alawi; Samsu Baharuddin, Azhari; Mohd Ali, Ahmad Amiruddin (2011)
A system for evaporating final discharged wastewater generated in a palm oil mill comprising removal of wastewater grit, equalization and stabilization of steam, evaporation, collection of condensed steam and water vapour and, collection and distribution of clean water.